Study designs to investigate Nox1 acceleration of neoplastic progression in immortalized human epithelial cells by selection of differentiation resistant cells - Sattayakhom, Apsorn; Chunglok, Warangkana; Ittarat, Wanida; Chamulitrat, Walee (Redox Biology, 2014)
To investigate the role of NADPH oxidase homolog Nox1 at an early step of cell transformation, we utilized human gingival mucosal keratinocytes immortalized by E6/E7 of human papillomavirus (HPV) type 16 (GM16) to generate progenitor cell lines either by chronic ethanol exposure or overexpression with Nox1. Among several cobblestone epithelial cell lines obtained, two distinctive spindle cell lines - FIB and NuB1 cells were more progressively transformed exhibiting tubulogenesis and anchorage-independent growth associated with increased invasiveness. These spindle cells acquired molecular markers of epithelial mesenchymal transition (EMT) including mesenchymal vimentin and simple cytokeratins (CK) 8 and 18 as well as myogenic alpha-smooth muscle actin and caldesmon. By overexpression and knockdown experiments, we showed that Nox1 on a post-translational level regulated the stability of CK18 in an ROS-, phosphorylation- and PKCepilon-dependent manner. PKCepilon may thus be used as a therapeutic target for EMT inhibition. Taken together, Nox1 accelerates neoplastic progression by regulating structural intermediate filaments leading to EMT of immortalized human gingival epithelial cells.